Incorporation of Magnetic Nanoparticles into Protoplasts of Microalgae Haematococcus pluvialis: A Tool for Biotechnological Applications - Maria G. Savvidou; Angelo Ferraro; Evangelos Hristoforou; Diomi Mamma; Dimitris Kekos; Fragiskos N. Kolisis (Molecules, 2020)
Intensive research on the use of magnetic nanoparticles for biotechnological applications of microalgae biomass guided the development of proper treatment to successfully incorporate them into these single-cell microorganisms. Protoplasts, as cells lacking a cell wall, are extensively used in plant/microalgae genetic manipulation as well as various biotechnological applications. In this work, a detailed study on the formation of protoplasts from Haematococcus pluvialis with the use of enzymatic and mechanical procedures was performed. The optimization of several parameters affecting the formation of protoplasmic cells and cell recovery was investigated. In the enzymatic treatment, a solution of cellulase was studied at different time points of incubation, whereas in the mechanical treatment, glass beads vortexing was used. Mechanical treatment gave better results in comparison to the enzymatic one. Concerning the cell recovery, after the protoplast formation, it was found to be similar in both methods used; cell viability was not investigated. To enhance the protoplast cell wall reconstruction, different “recovery media” with an organic source of carbon or nitrogen were used. Cell morphology during all treatments was evaluated by electron microscopy. The optimal conditions found for protoplast formation and cell reconstruction were successfully used to produce Haematococcus pluvialis cells with magnetic properties.